Edukasi Peningkatan Pengetahuan Metode Kontrasepsi Jangka Panjang Pada Pasangan Usia Subur di Dusun Pondok Buak, Kecamatan Lingsar - Nurul Hikmah Annisa; Baiq Ricca Afrida; Ni Putu Aryani; Susilia Idyawati (Indonesian Journal of Midwifery (IJM), 2022)
Family planning is a national scale program to reduce the birth rate and control the population in a country. This method is very effective for both delaying, spacing or terminating pregnancy. Therefore, the government is trying to increase the use of long-term contraceptive methods (MKJP) but in fact there are more users of Non-MKJP contraception than the use of Long-Term Contraceptive Methods (MKJP). The background of holding this "MKJP" counseling is that in fact there are still many people who do not fully understand what MKJP (Long Term Contraceptive Method) is. The purpose of this activity is to increase the knowledge and interest of participants regarding Long Term Contraception Methods. Of the 26 PUS attending the counseling, 15 people (58.00%) had less knowledge about MKJP and 11 people (42.00%) had good knowledge about MKJP. The material presented is the understanding, benefits, limitations, targets, time of use, advantages and side effects of each type of long-term contraceptive. The method used is a questionnaire. After the presentation of the material, there was a question and answer session where all participants were given the opportunity to ask questions related to the material and tell their experiences in using contraceptives. In addition to the question and answer session after the delivery of the material, a questionnaire was given. The results obtained after this activity were the participants' knowledge and understanding of the Long-Term Contraceptive Method. After being given counseling there was an increase, namely 24 people (92.3%) had good knowledge after being given counseling while 2 people (7.7) mothers had less knowledge after being given counseling. Therefore, with the extension of this family planning program as an effort to increase public knowledge and awareness about the importance of making the family planning program (KB) a success.Family planning is a national scale program to reduce the birth rate and control the population in a country. This method is very effective for delaying, spacing or terminating pregnancy. Therefore, the government is trying to increase the use of long-term contraceptive methods (MKJP) but in fact the use of Non-MKJP contraceptives is more than the use of long-term contraceptive methods (MKJP). The background of holding this "MKJP" counseling is that in fact there are still many people who do not fully understand what MKJP (Long Term Contraceptive Method) is. The purpose of this activity is to increase the knowledge and interest of participants regarding Long Term Contraception Methods. Of the 26 PUS who delivered counseling, 15 people (58.00%) had poor knowledge about MKJP and 11 people (42.00%) had good knowledge about MKJP. The material presented is the understanding, benefits, limitations, targets, time of use, advantages and side effects of each type of long-term contraceptive. The media used in this research is Power Point. The method used is a questionnaire with a checklist. After sending the material, there was a question and answer session where all participants were given the opportunity to ask questions related to the material and tell their experiences in using contraceptives. In addition to the question and answer session after the delivery of the material, a questionnaire was given. The results obtained after this activity were the participants' knowledge and understanding of the Long Term Contraception Method. After being given counseling, 24 people (92.3%) had good knowledge after being given counseling, 2 people (7.7) mothers had less knowledge after being given counseling. Therefore, with the extension of this family planning program as an effort to increase public knowledge and awareness about the importance of the success of the family planning program (KB).AbstrakKeluarga berencana adalah program skala nasional untuk menekan angka kelahiran dan mengendalikan penduduk di suatu Negara. Metode ini sangat efektif digunakan baik untuk menunda, menjarangkan ataupun menghentikan kehamilan. Oleh karena itu pemerintah berusaha untuk meningkatkan penggunaa metode kontrasepsi jangka panjang (MKJP) tetapi faktanya pemakai kontrasepsi Non MKJP lebih banyak dibandingkan pemakain Metode Kontrasepsi Jangka Panjang (MKJP). Latar belakang diadakannya penyuluhan â€œMKJPâ€ ini adalah bahwa faktanya masih banyak orang yang belum mengetahui secara keseluruhan tentang apa itu MKJP (Metode Kontrasepsi Jangka Panjang). Tujuan dilakukan kegiatan ini yaitu meningkatkan pengetahuan dan minat peserta mengenai Metode Kontrasepsi Jangka Panjang. Dari 26 PUS yang menghadari penyuluhan yang memiliki pengetahuan kurang tentang MKJP yaitu 15 orang (58,00%) dan yang mempunyai penegtahuan baik tentang MKJP yaitu 11 orang (42,00%). Materi yang disajikan yaitu pengertian, manfaat, keterbatasan, sasaran, waktu penggunaan, kelebihan dan efek samping tentang masing-masing jenis alat kontrasepsi jangka panjang. Media yang digunakan dalam penelitian ini adalah Power Point. Metode yang digunakan yaitu kuesioner dengan ceklist. Setelah penyampaian materi dilanjutkan sesi tanya jawab dimana semua peserta di berikan kesempatan untuk bertanya terkait materi dan menceritakan pengalamannya dalam penggunaan alat kontrasepsi. Selain sesi tanya jawab setelah penyampaian materi diberikan kuesioner. Hasil yang di dapatkan setelah kegiatan ini yaitu pengetahuan dan pemahaman peserta mengenai tentang Metode Kontrasepsi Jangka Panjang. Setelah diberikan penyuluhan terdapat peningkatan yaitu 24 orang (92,3%) memiliki pengetahuan yang baik setelah diberikan penyuluhan sedangkan 2 orang (7,7) ibu memiliki pengetahuan kurang setelah diberikan penyuluhan. Oleh karena itu, dengan adanya penyuluhan program keluarga berencana ini sebagai upaya meningkatkan pengetahuan dan kesadaran masyarakat tentang pentingnya untuk mensukseskan program keluarga berencana (KB).